METODE PEMBELAJARAN ROLE PLAYING DALAM MENINGKATKAN KETERAMPILAN BERBICARA (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The historical past of this research is the low speakme competencies of students at primary faculty level. This study targets to observe the impact of the role playing getting to know approach on college students' talking capabilities in class IV Indonesian at SD Negeri Leuwiliang 04. The studies method used is quantitative with an simplest manipulate institution design, the sample studied turned into 20 college students. testing in research uses assemble validity checks and reliability exams. records analysis used the unbiased samples T-check after going through the prerequisite test ranges including normality exams and homogeneity assessments. The results of these studies received from the impartial samples T-test that the importance cost (2-tailed) turned into 0.000, so Ho became rejected and Ha became typical. Based totally on the outcomes of the studies and calculations above, it suggests that the function gambling getting to know approach has a large impact on students' speaking abilities